2021
DOI: 10.1039/d1ma00024a
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-iron layered double hydroxides for an improved Ni/Fe hybrid battery-electrolyser

Abstract: The transition to renewable electricity sources and green feedstock implies the development of electricity storage and conversion systems to both stabilise the electricity grid and to provide electrolytic hydrogen. We...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The Ni(OH)2 has two naturally occurring crystalline polymorphs-the hydrotalcitelike α-phase and the brucite-like β-phase (Figure 4). The α-phase is composed of positively charged Ni(OH)2 layers where water molecules and anions (typically counter-ions of Ni salts used for electrode synthesis) intercalate [18,35]. When charging, the α-Ni(OH)2 undergoes a transformation to γ-NiOOH with little volume change due to their similar structure and interstitial spacing (~7 Å) [57].…”
Section: Positive Electrodementioning
confidence: 99%
See 2 more Smart Citations
“…The Ni(OH)2 has two naturally occurring crystalline polymorphs-the hydrotalcitelike α-phase and the brucite-like β-phase (Figure 4). The α-phase is composed of positively charged Ni(OH)2 layers where water molecules and anions (typically counter-ions of Ni salts used for electrode synthesis) intercalate [18,35]. When charging, the α-Ni(OH)2 undergoes a transformation to γ-NiOOH with little volume change due to their similar structure and interstitial spacing (~7 Å) [57].…”
Section: Positive Electrodementioning
confidence: 99%
“…This α↔γ transformation yields a high electron transfer of ~1.67 [58], which contributes to the high theoretical energy density of α-Ni(OH)2 of around 482 mAh g −1 [35]. While this is an impressive feat, the α-Ni(OH)2 is less preferred as cathode material The α-phase is composed of positively charged Ni(OH) 2 layers where water molecules and anions (typically counter-ions of Ni salts used for electrode synthesis) intercalate [18,35]. When charging, the α-Ni(OH) 2 undergoes a transformation to γ-NiOOH with little volume change due to their similar structure and interstitial spacing (~7 Å) [57].…”
Section: Positive Electrodementioning
confidence: 99%
See 1 more Smart Citation
“…The calcination of mixed hydroxides leads to mixed oxide materials that show very interesting features . Their acid–base sites and redox properties can be tailored for specific applications in catalysis, water splitting, biosorbents, fire retardancy, and electrochemistry. Also, Ni–Fe LDHs have attracted particular interest in electrochemical applications because of their low cost, good redox activity, and eco-friendly properties. , Various reported studies showed that Ni–Fe LDHs have good electrocatalytic activity in electrochemical sensing applications. …”
Section: Introductionmentioning
confidence: 99%
“…40−46 Also, Ni−Fe LDHs have attracted particular interest in electrochemical applications because of their low cost, good redox activity, and eco-friendly properties. 47,48 Various reported studies showed that Ni−Fe LDHs have good electrocatalytic activity in electrochemical sensing applications. 49−52 The aims of this work were to synthesize a Ni−Fe layered double hydroxide (Ni−Fe LDH) nanosheet and assess its applicability for the modification of a screen-printed electrode (SPE).…”
Section: ■ Introductionmentioning
confidence: 99%